Photovoltaics: Passivation of Interfaces in Thin Film Solar Cells: Understanding the Effects of a Nanostructured Rear Point Contact Layer (Adv. Mater. Interfaces 2/2018). Issue 2 (24th January 2018) - Salomé, Pedro M. P.; Vermang, Bart; Ribeiro‐Andrade, Rodrigo; Teixeira, Jennifer P.; Cunha, José M. V.; Mendes, Manuel J.; Haque, Sirazul; Borme, Jêrome; Águas, Hugo; Fortunato, Elvira; Martins, Rodrigo; González, Juan C.; et al.
Abstract : On the left a schematic of an ultrathin Cu(In, Ga)Se2 solar cell with passivated rear interface and on the right a transmission electron microscopy of the real device. In article number1701101 Pedro M. P. Salomé and co‐workers show a significant reduction in the rear recombination, improving the electrical performance of solar cells.